Changes in Families' Caregiving Experiences through Involvement as Participants then Facilitators in a Family Peer‐Education Program for Mental Disorders in Japan. Issue 2 (2nd November 2015) - Kageyama, Masako; Yokoyama, Keiko; Nakamura, Yukako; Kobayashi, Sayaka
Abstract : A family peer‐education program for mental disorders was developed in Japan, similar to existing programs in the United States and Hong Kong. Families that serve as facilitators in such programs may enhance their caregiving processes and, thereby, their well‐being. This study's aim was to describe how families' caregiving experiences change, beginning with the onset of a family member's mental illness, through their involvement in a family group or peer‐education program as participants then facilitators. Thus, this study was conducted in a family peer‐education program for mental disorders in Japan. Group interviews were conducted with 27 facilitators from seven program sites about their experiences before, during, and after becoming facilitators. Interview data were coded and categorized into five stages of caregiving processes: (1) withdrawing and suppressing negative experiences with difficulty and regret; (2) finding comfort through being listened to about negative experiences; (3) supporting participants' sharing as facilitators; (4) understanding and affirming oneself through repeated sharing of experiences; and (5) finding value and social roles in one's experiences. The third, fourth, and fifth stages were experienced by the facilitators. The value that the facilitators placed on their caregiving experiences changed from negative to positive, which participants regarded as helpful and supportive. We conclude that serving as facilitators may improve families' caregiving processes. Abstract : Video Abstract